Past and present seroprevalence and disease burden estimates of Toxoplasma gondii infections in Germany: An appreciation of the role of serodiagnostics - Frank Seeber (Elsevier, 2023)
Toxoplasmosis is one of the major foodborne parasitic diseases in Germany, with 49% of its population chronically infected with its causative agent, Toxoplasma gondii. Although the acute disease is usually benign in immunocompetent individuals, it is a threat for immunocompromised patients as well as for fetuses of seronegative mothers. As a result of infection, congenital and ocular toxoplasmosis can have serious lifelong consequences. Here I will highlight the epidemiologic situation, from its past in the two separate parts of Germany, to its unification 30 years ago and up to the present day. The main identified risk factor for infection in Germany is thought to be the consumption of undercooked or raw meat or sausages. However, the relative impact of this risky eating habit as well as that of other risk factors are changing and are discussed and compared to the situation in the Netherlands. Finally, the importance of robust and efficient high-throughput serological assays for obtaining reliable epidemiological data, on which public health decisions can be made, is highlighted. The potential of bead-based multiplex assays, which allow the incorporation of multiple antigens with different analytical properties and thus yield additional information, are described in this context. It illustrates the interdependence of new analytic assay developments and sound epidemiology, a foundation that decades-old data from Germany did not have.